A Seascape Genomics Perspective on Restrictive Genetic Connectivity Overcoming Signals of Local Adaptations in the Green Abalone (Haliotis fulgens) of the California Current System - Jorge Alberto Mares‐Mayagoitia; Paulina Mejía‐Ruíz; Fabiola Lafarga‐De la Cruz; Fiorenza Micheli; Pedro Cruz‐Hernández; Juan A. De‐Anda‐Montañez; John Hyde; Norma Y. Hernández‐Saavedra; Vladimir S. De Jesús‐Bonilla; Carmen E. Vargas‐Peralta; Ana L. Flores‐Morales; Alejandro F. Pares‐Sierra; et al. (Ecology and Evolution, 2025)
ABSTRACT Seascape genomics facilitates integrative research on eco‐evolutionary forces, such as migration and natural selection, which shape genomic connectivity and structure and provide critical insights for conservation strategies. The green abalone (Haliotis fulgens) is distributed from California, United States, to Baja California Sur, Mexico, and exposed to a latitudinal environmental gradient in the California Current System. This study aimed to investigate genomic population structure and potential local adaptations of green abalone across its distribution. The green abalone exhibits a distinctive neutral genetic structuring influenced by geographic distance and marine currents rather than local adaptations. Analyses using 9100 neutral and 17 outlier SNPs revealed three distinct populations: the North group (California to Ensenada, Baja California), a population on Guadalupe Island, and the South group (coastal locations of the Baja California peninsula). The research underscores the significance of life history traits and larval dispersal in shaping genetic connectivity. Connectivity appears to be influenced by geographic distance on neutral genetic structure, overshadowing natural selection's role. Furthermore, no genome–environment associations to sea surface temperature values were found. Future research should integrate genetic data with ocean circulation modeling to better understand the mechanisms and outcomes of larval dispersal and genetic connectivity. This study emphasizes the importance of both local and binational (USA‐Mexico) conservation efforts, suggesting the development of SNP marker panels for traceability and management. Collaborative strategies could serve as models for binational conservation initiatives in other ecoregions, promoting sustainable management and conservation of green abalone populations and other exploited species across national borders.